The Role of m6A Ribonucleic Acid Modification in the Occurrence of Atherosclerosis - Fu, Jie; Cui, Xinghui; Zhang, Xiaoyun; Cheng, Min; Li, Xiaoxia; Guo, Zhiliang; Cui, Xiaodong (Frontiers in Genetics, 2021)
The N6-methyladenosine (m6A) modification is the most abundant epitranscriptomic modification in eukaryotic messenger RNA (mRNA). The m6A modification process is jointly regulated by various enzymes and proteins, such as methyltransferases, demethylases and related m6A-binding proteins. The process is dynamic and reversible, and it plays an essential role in mRNA metabolism and various biological activities. Recently, an increasing number of researchers have confirmed that the onset and development of many diseases are closely associated with the molecular biological mechanism of m6A RNA methylation. This study focuses on the relationship between m6A RNA modification and atherosclerosis (AS). It thoroughly summarizes the mechanisms and processes of m6A RNA modification in AS-related cells and the relationships between m6A RNA modification and AS risk factors, and it provides a reference for exploring new targets for the early diagnosis and treatment of AS.